Synthesis and anti-inflammatory activity of novel 1,2,3-triazole- derivatives from 7-Oxodehydroabietic acid - Yong-Feng Lv; Fu-Cai Ren; Kang Hui; Jie Zheng; Shou-Jin Liu; Han Luo (BMC Chemistry)
Abstract Dehydroabietic acid (DHA) is a naturally occurring diterpene with relevant biological activities. 7-Oxodehydroabietic acid as a highly oxidized state derivative from Dehydroabietic acid (DHA) showing good activities. However, the reported compounds did not include triazole derivatives. To discover novel potent anti-inflammatory diterpenoids, a series of hybrids of 7-Oxodehydroabietic acid containing 1,2,3-triazole moiety were designed and synthesized. The anti-inflammatory activity of the new compounds was assessed towards BV2 cell lines using L-NMMA (IC50 = 42.36 ± 2.47 µM) as a positive control. Compared with the L-NMMA, anti-inflammatory effect (NO inhibitory activities) was found in these novel molecules, especially compounds 9 (IC50 = 8.00 ± 0.83 µM), 10 (IC50 = 8.44 ± 0.89 µM), 15 (IC50 = 8.13 ± 0.97 µM) and 16 (IC50 = 8.84 ± 1.10 µM). The anti-inflammatory activity of compounds 9, 10, 15 and 16 in vivo are underway.